2009
DOI: 10.1136/hrt.2008.153965
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cavotricuspid isthmus block during atrial fibrillation ablation in patients without atrial flutter: a randomised controlled trial

Abstract: It was not possible to demonstrate any beneficial effect of CTIB in addition to CPVA with regard to AFL or AF recurrences during follow-up. Repetitive long-term Holter monitoring demonstrated a 33% rate of freedom from AF during a 1-year follow-up. Including additional CPVA procedures, a clinical effect was noted in 62% of the patients at 12 months. Patients with AF or AFL recurrences were often asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…There were 2 studies that studied the utility of a CTI line in a randomized fashion 26,27 . No difference in relative risk was observed with the addition of a CTI line to PVI/CPVA in either paroxysmal or persistent AF with a RR of 1.02 (95% CI 0.76, 1.37) and 1.00 (95% CI 0.54, 1.84), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies that studied the utility of a CTI line in a randomized fashion 26,27 . No difference in relative risk was observed with the addition of a CTI line to PVI/CPVA in either paroxysmal or persistent AF with a RR of 1.02 (95% CI 0.76, 1.37) and 1.00 (95% CI 0.54, 1.84), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized trial, 149 patients with paroxysmal and persistent AF and no history of CTI-AFL were evaluated for any incremental benefit of prophylactic CTI ablation in addition to CPVA. There were no differences observed in the cumulative CTI-AFL or AF-free rate between the two treatment groups [77]. Moreover, it has been demonstrated that the triggers for both AF and AFL may originate in the PVs, and disconnection of the PVs may eliminate the need for further ablation.…”
Section: Ablation Of Cavotricuspid Isthmusmentioning
confidence: 80%
“…That study randomized patients to PVI and empirical CTI versus PVI alone. At 12‐month follow‐up there was no difference in the cumulative AF‐free rate between both groups ( P = .71) . It was not possible to demonstrate any beneficial effect of CTI in addition to PVI with regard to atrial flutter (AFL) or AF recurrences during follow‐up .…”
mentioning
confidence: 93%
“…Subsequently, two recent RCTs have consistently reported that ablation of Rotors has no incremental benefit on all‐atrial arrhythmia recurrence. Pontoppidam et al in 2009 conducted a small ( n = 149) RCT assessing the role of empirical cavotricuspid isthmus (CTI) line in patients with AF (54% paroxysmal) undergoing catheter ablation . That study randomized patients to PVI and empirical CTI versus PVI alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation